2016
DOI: 10.1094/pdis-05-16-0598-re
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Nano-Formulated Zinc Oxide for Control of Citrus Canker on Grapefruit Trees

Abstract: Antimicrobial activity of experimental formulations of two structurally different nano-zinc oxide materials, plate-like Zinkicide SG4 and particulate Zinkicide SG6, was evaluated against Xanthomonas citri subsp. citri, the cause of citrus canker. In vitro assay demonstrated Zinkicide SG4 had a twofold lower minimum inhibitory concentration (MIC) against Escherichia coli and X. alfalfae subsp. citrumelonis (62.5 to 250 µg/ml) compared with copper sulfate (250 µg/ml), copper hydroxide (250 to 500 µg/ml), or cupr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 28 publications
0
72
0
Order By: Relevance
“…Integration of ASM with copper has been demonstrated to protect crops in which copper-resistant pathogen strains predominate, as was reported for the management of bacterial speck and bacterial spot of tomato (Louws et al, 2001). Other chemicals that have been successfully tested but, for different reasons, are not widely used for CC control are streptomycin and zinc oxide (Behlau et al, 2012b;Graham et al, 2007Graham et al, , 2010Graham et al, , 2016b.…”
Section: Management Of CCmentioning
confidence: 97%
“…Integration of ASM with copper has been demonstrated to protect crops in which copper-resistant pathogen strains predominate, as was reported for the management of bacterial speck and bacterial spot of tomato (Louws et al, 2001). Other chemicals that have been successfully tested but, for different reasons, are not widely used for CC control are streptomycin and zinc oxide (Behlau et al, 2012b;Graham et al, 2007Graham et al, , 2010Graham et al, , 2016b.…”
Section: Management Of CCmentioning
confidence: 97%
“…The results in the same line of Abd El-Hai et al (2009) and Hamaza et al (2013), they reported that, Zn NPs suppressed damping off, charchol rot diseases in sunflower and control of late wilt disease of maize and enhancement of yield, respectively. Moreover, Singh et al (2013) added that, NPs of CuSO 4 and Na 2 B 4 O 7 controlled rust disease of field peas, while Zn NPs spraying led to reducing of canker lesion and scab of grapefruit and melanose (Graham et al 2016). Panwar et al (2012) added that, Zn plays a vital role for plant diseases concerned to its deficiency and improved growth and yield.…”
Section: -Effect Of Nanoparticls Of Cercospora Leaf Spot Diseasementioning
confidence: 99%
“…Also, Abd-El-Hai et al (2009) added that, Mg and Zn NPs suppressed the damping off and charcoal rot disease in sunflower. Additionally, Graham et al (2016) showed that, ZnNPs (zinkicide) spraying led to reducing of grapefruit canker lesion development and incidence than bacteriocide cuprous and Zn oxide also effective against fungal disease i.e. grapefruit scab and melanose.…”
Section: Introductionmentioning
confidence: 99%
“…Since the list of these promising compounds and techniques is expanding at a fast pace under the urgency created by HLB, I want to highlight here only two examples of them that have sparked great interest in Florida: The first technology consists of nanooxide materials (known as Zinkicide). These nanoparticles are able to control certain diseases such as canker in citrus better than conventional copper-based methods and present advantages such as lower toxicity, higher antimicrobial activity and ability to move translaminar in the plant [21]. Recently, it has been shown by cuban researchers the potential of a relatively newly described group of hormones, brassinosteroids, for controlling HLB both in already infected plants and with potential as a protective treatment measure for nursery plants before planting in the grove.…”
Section: New Treatmentsmentioning
confidence: 99%